2013
DOI: 10.1128/aac.02102-12
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Antibiotic Resistance and Molecular Characterization of Integrons among Shigella Isolates in Eastern China

Abstract: A total of 747 Shigella isolates were collected from hospitals in Jiangsu Province of China. Susceptibilities to antimicrobials and integrons were tested. A total of 78.3% of S. flexneri isolates and a total of 74.3% S. sonei isolates were resistant to at least three antibiotics. Of the Shigella isolates, 74.7% had integron I and 82.6% had integron II. The conjunction of the high prevalence of integrons in Shigella and high resistance to antimicrobials will lead to rapid dissemination of resistant genes in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 20 publications
2
17
1
Order By: Relevance
“…Thus, additional studies are needed in order to go further in this determination. In contrast to other studies [17,32] Serotype 6 in contrast, showed more heterogeneity, with scattered isolates in different PFGE patterns. Similarly, isolates with the same antibiotic resistance profile were found in different PFGE and vice-versa; however, MDR isolates were more frequently found in clusters suggesting a possible clonal spreading.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, additional studies are needed in order to go further in this determination. In contrast to other studies [17,32] Serotype 6 in contrast, showed more heterogeneity, with scattered isolates in different PFGE patterns. Similarly, isolates with the same antibiotic resistance profile were found in different PFGE and vice-versa; however, MDR isolates were more frequently found in clusters suggesting a possible clonal spreading.…”
Section: Discussioncontrasting
confidence: 99%
“…In the USA during 2000-2010 [28], resistance rates to the common drugs nalidixic acid (1%), tetracycline (18%) and SXT (33%) were dramatically lower than those observed in the current study, whilst ampicillin had a similar resistance rate of 74%. In addition, in Eastern China high levels of resistance to ampicillin (70.8%), nalidixic acid (69.3%), tetracycline (74.8%) and SXT (73.8%) were reported [9]. The widespread nature of nalidixic acid and fluoroquinolone resistance has been documented in many countries [29,30].…”
Section: Yearmentioning
confidence: 99%
“…Bacterial molecular typing is frequently applied for outbreak surveillance and phylogenetic investigation. Strain-specific fingerprints generated are used to facilitate the identification of disease transmission routes and sources [7][8][9][10][11]. To date, various genotyping methods including biotyping, multilocus variable-number tandem-repeat analysis (MLVA) and PFGE have been used for the epidemiological investigation of S. sonnei [31,32].…”
Section: Yearmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of ESBLs is the major defense mechanism against third-generation cephalosporins employed by Enterobacteriaceae, including Shigella species. Recent reports from Jiangsu and Anhui Provinces located in eastern China, which neighbor Shanghai, showed that the rates of resistance to CTX were 21.5 % and 26.4 %, respectively, among Shigella isolates [14,15]. Therefore, the high prevalence of ESBL-producing Shigella isolates in eastern China is a threat to public health, and tracking and monitoring of the rapid spread of ESBL producers is urgently required.…”
Section: Discussionmentioning
confidence: 99%